2014
DOI: 10.1016/j.jad.2013.04.045
|View full text |Cite|
|
Sign up to set email alerts
|

Omega-6 fatty acids and greater likelihood of suicide risk and major depression in early pregnancy

Abstract: Objective To estimate the prevalence of suicide risk (SR) and major depressive episode (MDE) in early pregnancy, and the relationship of fatty acids serum status to these outcomes. Method Cross-sectional analyses of 234 pregnant women enrolled in a prospective cohort study in Rio de Janeiro/Brazil were performed. SR and MDE were defined according to MINI International Neuropsychiatric Interview. Fatty acids compositions were determined in serum samples obtained between the 6th and 13th gestational week. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In two recent studies, investigators evaluated associations between suicidal ideation during pregnancy and various biomarkers, finding interesting results (Farias et al, 2013, Vaz et al, 2014). In 2013, Farias et al (Farias et al, 2013) found that pregnant women with current suicide risk (assessed using the Mini International Neuropsychiatric Interview) had higher mean total cholesterol (169.2 vs. 159.2 mg/dL, p=0.017), high-density lipoprotein (HDL) (50.4 vs. 47.7 mg/dL , p=0.031), and low-density lipoprotein (LDL) (102.8 vs. 95.6 mg/dL, p=0.022) compared to those without current suicide risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent studies, investigators evaluated associations between suicidal ideation during pregnancy and various biomarkers, finding interesting results (Farias et al, 2013, Vaz et al, 2014). In 2013, Farias et al (Farias et al, 2013) found that pregnant women with current suicide risk (assessed using the Mini International Neuropsychiatric Interview) had higher mean total cholesterol (169.2 vs. 159.2 mg/dL, p=0.017), high-density lipoprotein (HDL) (50.4 vs. 47.7 mg/dL , p=0.031), and low-density lipoprotein (LDL) (102.8 vs. 95.6 mg/dL, p=0.022) compared to those without current suicide risk.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Farias et al (Farias et al, 2013) found that pregnant women with current suicide risk (assessed using the Mini International Neuropsychiatric Interview) had higher mean total cholesterol (169.2 vs. 159.2 mg/dL, p=0.017), high-density lipoprotein (HDL) (50.4 vs. 47.7 mg/dL , p=0.031), and low-density lipoprotein (LDL) (102.8 vs. 95.6 mg/dL, p=0.022) compared to those without current suicide risk. Furthermore, in 2014, Vaz et al (Vaz et al, 2014) reported a higher likelihood of suicide risk among pregnant women with higher serum omega-6 fatty acids: arachidonic acid (OR=1.45, 95% CI: 1.02–2.07) and adrenic acid (OR=1.43, 95% CI: 1.01–2.04). Recently Fung et al, (Fung et al, 2015) assessed the relation between antepartum depression and maternal early pregnancy serum brain-derived neurotrophic factor (BDF) concentration—a neurotrophin that is involved in neuronal cell growth, survival, and synaptic plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…were not associated with a hospitalization for a suicide attempt within 1 year after delivery ( 27 ). A cross-sectional analyses carried out on 234 pregnant women enrolled in a prospective cohort study in Brazil reported a higher likelihood of suicide risk among women with higher arachidonic acid and adrenic acid levels ( 39 ). Women who have had a postpartum psychiatric admission have a 70 times greater risk of suicide in their first postpartum year ( 40 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was previously reported that serum n -6 PUFA levels are inversely correlated with depression [9], but Wolfe and colleagues observed a positive association between dietary n -6 PUFA intake (and corresponding blood levels) and risk of severe depression [10]. Furthermore, data from a cross-sectional study in pregnant Brazilian women found that high serum levels of n -6 PUFAs were associated with a greater likelihood of depression [74]. …”
Section: Dietary Fat Regulation Of Brain Function and Links To Depmentioning
confidence: 99%